An investigation of secondary school teachers' flipped classroom readiness - Kazu, Ibrahim Yasar; Kurtoglu, Cemre (Education Assoc South Africa, 2022)
In the descriptive study reported on here we used A Scale for Flipped Classroom Readiness of Secondary School Learners developed by Hao and adapted by Durak to evaluate teachers' readiness. The scale was administered to 233 teachers working at 5 randomly selected secondary schools in the city of Elazig, Turkey. Five key aspects of their readiness to conduct flipped classroom education were investigated: self-efficacy in controlling learners, technological self-efficacy, self-efficacy for planning classroom time, readiness for preparatory work and being open-minded. In general, overall readiness was found to be positive for young teachers who had recently joined the profession. Teachers who owned computers and perceived themselves as being competent users of information and communications technology were more likely to have favourable opinions of their ability to implement flipped classroom pedagogy.
Keywords: flipped classroom; readiness for preparatory work; self-efficacy for planning classroom time; technology self-efficacy